Evaluation of the effects of phosphorylation of synthetic peptide substrates on their cleavage by caspase-3 and -7. Issue 12 (25th June 2021) - Maluch, Izabela; Grzymska, Justyna; Snipas, Scott J.; Salvesen, Guy S.; Drag, Marcin
Abstract : Caspases are a family of enzymes that play roles in cell death and inflammation. It has been suggested that in the execution phase of the apoptotic pathway, caspase-3, -6 and -7 are involved. The substrate specificities of two proteases (caspases 3 and 7) are highly similar, which complicates the design of compounds that selectively interact with a single enzyme exclusively. The recognition of residues other than Asp in the P1 position of the substrate by caspase-3/-7 has been reported, promoting interest in the effects of phosphorylation of amino acids in the direct vicinity of the scissile bond. To evaluate conflicting reports on this subject, we synthesized a series of known caspase-3 and -7 substrates and phosphorylated analogs, performed enzyme kinetic assays and mapped the peptide cleavage sites using internally quenched fluorescent peptide substrates. Caspases 3 and 7 will tolerate pSer at the P1 position but only poorly at the P2′ position. Our investigation demonstrates the importance of peptide length and composition in interpreting sequence/activity relationships. Based on the results, we conclude that the relationship between caspase-3/-7 and their substrates containing phosphorylated amino acids might depend on the steric conditions and not be directly connected with ionic interactions. Thus, the precise effect of phospho-amino acid residues located in the vicinity of the cleaved bond on the regulation of the substrate specificity of caspases remains difficult to predict. Our observations allow to predict that natural phosphorylated proteins may be cleaved by caspases, but only when extended substrate binding site interactions are satisfied.